Real-life efficacy and safety of oral propranolol for ocular adnexal infantile hemangiomas: observational cohort study - Stefano Malvindi; Elena Sammarco; Andrea Elefante; Vittoria Lanni; Domenico Cicala; Francesco Esposito; Ciro Picardi; Adriana Iuliano; Dana Cohen; Giuseppe Mariniello; Antonella D’Aponte; Ciro Costagliola; et al. (Frontiers in Ophthalmology)
ObjectiveTo assess the effectiveness and safety of oral propranolol for the treatment of ocular adnexal infantile hemangiomas.Patients and methodsretrospective observational cohort study. Propranolol was administered at an initial oral dose of 1 mg/kg and subsequently increased to 2 mg/kg for 1 year. Outcomes were evaluated by comparing pre- and post-treatment clinical findings, contrast-enhanced ultrasound (CEUS) findings and/or orbital magnetic resonance imaging findings from baseline to 3, 6, 9, 12, 24, and 48 weeks. Regression was graded as follows: satisfactory when 90% and above of the baseline lesion volume and extension decreased, acceptable when 50 to 90%, mediocre when 30 to 50%, poor less than 30%.ResultsTwenty-four patients were included in this study. The mean age at presentation was 4 ± 1 week. Sixteen (71%) patients were females and 7 (29%) were males. The mean follow-up duration was 18 ± 3 months. Therapy was started for of 23/24 patients at 5 weeks old, of 1/24 started at 9 weeks of age. The median age was 5,16 weeks. Sixteen patients (66%) had satisfactory resolution between 3 and 6 weeks, 5 (20%) after 9 weeks, and 3 (12%) after 12 weeks. One patient (5%) had a mediocre response after 24 weeks. One patient withdrew from therapy because of hypoglycemia, which was successfully managed as an outpatient. No significant adverse reactions, such as bradycardia, hypotension, bronchospasm, or congestive heart failure, were detected in this cohort.ConclusionThis study indicates that the real-life use of oral propranolol for infantile hemangioma yields a high success rate with a lower morbidity than previously reported, particularly when managed by a proficient and multidisciplinary team.